Relationship between flexural strength and pore structure of pavement concrete under fatigue loads and Freeze-thaw interaction in seasonal frozen regions. (20th June 2018) - Shen, Aiqin; Lin, Senlin; Guo, Yinchuan; He, Tianqin; Lyu, Zhenghua
Highlights: Interaction function of fatigue load and freeze–thaw on pore-structure is investigated. The properties of pore-structure and flexural strength are studied. Interaction effect accelerates the deterioration rate of the pore-structure. The relationship between flexural strength and pore structure is analyzed using gray relational analysis. Abstract: To explore the correlation between the flexural strength decay and the pore structure evolution of pavement concrete in seasonal frozen regions, 4 stages of an interaction experimental scheme were designed. The characteristic parameters of pore structure under the interactions were quantitatively characterized, and the correlation between the flexural strength decay and the microstructure evolution was discussed. The results show that the flexural strength of concrete under this interaction presents a parabolic attenuation trend. The specific surface area, the most probable aperture and the less harmful pores were the most important microstructure parameters affecting the flexural strength of concrete; their gray correlations were 0.8 or greater. Further, the regression analysis shows that there is a good linear relationship between the flexural strength attenuation and the pore structure evolution; the regression coefficient reaches 0.845.